2007
DOI: 10.1038/sj.ejcn.1602759
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the glycaemic index of an evening meal on substrate oxidation following breakfast and during exercise the next day in healthy women

Abstract: Objective: To investigate whether the 'overnight second-meal effect' results in altered substrate oxidation during the postprandial period following breakfast and subsequent sub-maximal exercise in women. Subjects/Methods: Seven recreationally active women were recruited for the study. In each trial, participants were provided with their evening meal on day 1, which was composed of either high glycaemic index (HGI) or low glycaemic index (LGI) carbohydrates (CHO). On day 2, participants were provided with a st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
24
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 36 publications
(46 reference statements)
1
24
0
Order By: Relevance
“…Each exercise session was designed to be equal both in intensity and duration. These exercise sessions have been shown to induce a significant increase in fat oxidation [37,38] and have been used in previous studies in healthy women [14,39]. During the exercise period, heart rate was monitored continuously by a radio telemetry monitor (Polar vantage NV, Kemple, Finland); blood samples drawn and subjective scales were taken at 15 minute intervals; and expired air samples were obtained continuously.…”
Section: Experimental Protocolmentioning
confidence: 99%
“…Each exercise session was designed to be equal both in intensity and duration. These exercise sessions have been shown to induce a significant increase in fat oxidation [37,38] and have been used in previous studies in healthy women [14,39]. During the exercise period, heart rate was monitored continuously by a radio telemetry monitor (Polar vantage NV, Kemple, Finland); blood samples drawn and subjective scales were taken at 15 minute intervals; and expired air samples were obtained continuously.…”
Section: Experimental Protocolmentioning
confidence: 99%
“…In addition, if the breakfast has a particularly high glycaemic 424 index, then an elevated pre-exercise muscle glycogen concentration (70) can also contribute to a 425 further suppression of fat oxidation in both men (71) and women (72) .…”
mentioning
confidence: 99%
“…Taking the above example, some studies have 65 included only solid foods as breakfast irrespective of the many highly calorific beverages 66 available, yet (notwithstanding differences in gastric emptying rate and metabolic response to 67 different nutrients in solid versus liquid form (6) , our net energy balance does not discriminate between absorbed nutrients or calories depending on whether they require chewing -a calorie is 69 a calorie. 70 While in the future it might become possible to justify a rationale for defining meals 71 based on a certain mixture of nutrients, a logical starting point to define the essential conditions 72 of breakfast per se would be based on the quantity and timing of energy consumed. We propose 73 that a quantity of 50 kcal represents an appropriate arbitrary threshold to exclude common 74 ingestive behaviours that would neither be recognised as a 'meal' by the majority of people nor 75 meaningfully shift our physiology towards the fed-state, a marker of which could be a detectable 76 perturbation in exogenous and/or endogenous substrate utilisation (thus one standard tea/coffee 77 would be unlikely to meet this criterion).…”
mentioning
confidence: 99%
“…Similarly, the II of HR was significantly lower than UBR (P ¼ 0.007) and this finding could be because of the higher content of NSP in HR (Po0.001, Table 1) compared with UBR. It is evident that NSP-rich foods may have a role in the reduced insulinaemic response (Jenkins et al, 2000;Stevenson et al, 2008) and their beneficial effect in reducing the risk of developing diabetes has been extensively studied in large cohort epidemiological studies. Indeed, many studies have shown a significant association between dietary NSP and reduced risk of diabetes (Salmeron et al, 1997;Meyer et al, 2000;Stevens et al, 2002;Schulze et al, 2004).…”
Section: Discussionmentioning
confidence: 99%